Climbing ability of Tribolium castaneum (Herbst) and T. confusum J. du Val on food packaging materials (Bollettino di zoologia agraria e bachicoltura, 2024)
Climbing ability of Tribolium castaneum and T. confusum was tested by placing on wood props with different angles (0, 30, 45, 60 and 90c) stripes (5x10 cm) of packaging materials. Tests were carried out at 22±1 cc and at 27±1 cc, 60±10% r.h., in a chamber with natural light, conditions usually recorded in stores and processing departments. The two species climbed corrugated paper placed on wood props with angles of 30, 45, 60, and 90c. On the other tested materials, from an angle of 30c, they showed a scarce ability to climb. Sometimes the two species appeared to display different climbing ability. However this indication was not supported by the results of the statistical analysis.
Keywords: Red flour beetle; Confused flour beetle; movement; materials